Paleoenvironments of the Shungura Formation (Plio-Pleistocene: Ethiopia) based on ecomorphology of the bovid astragalus. Issue 88 (November 2015) - Barr, W. Andrew
Abstract: The Shungura Formation in southwestern Ethiopia preserves a long and relatively continuous record of eastern African mammalian and hominin evolution. This study reconstructs habitat preferences of the Shungura Formation bovids from ca. 3.4–1.9 Ma (million years ago), based on the ecomorphology of fossil bovid astragali. Habitat predictions are made using a Discriminant Function Analysis informed by functional analysis of the astragalus that controls for body size and phylogenetic signal. The high abundance of astragali in the Shungura record allows for habitat reconstructions on sub-unit timescales, rather than aggregating samples at the level of geological member. During much of the time period examined, the lower Omo Valley was dominated by relatively mesic habitats in close proximity to the ancestral Omo River. Previous research has suggested that environmental change at ∼2.85 Ma caused significant habitat change at Shungura, but the astragalar data do not support major habitat change at this time. However, there are significant fluctuations in inferred habitats, with more open habitats indicated in sub-units C-08 and C-09 (∼2.56 Ma), and in unit F-01 (just after 2.36 Ma). The cause of sub-unit fluctuations in habitat signal is difficult to determine, but local factors, including spatial habitat heterogeneity around the river channel and in its floodplain, may play a contributing role. In the light of faunal evidence from elsewhere in the greater Omo-Turkana Basin, hominins in the area likely had access to a variety of heterogeneous habitats.